ZSM-5 Filled Polyether Block Amide Membranes for Separating EA from Aqueous Solution by Pervaporation - Jin Gu; Xinran Zhang; Yunxiang Bai; Le Yang; Chunfang Zhang; Yuping Sun (International Journal of Polymer Science)
ZSM-5 filled polyether block amide membranes (PEBA), PEBA/ZSM-5, were prepared and used to recover aroma, ethyl acetate (EA), from aqueous solution by pervaporation (PV). The membranes demonstrated high EA permselectivity, and with the increase of ZSM-5 loading, the separation factor increased initially and then decreased, while the total flux demonstrated the similar variation until the ZSM-5 loading was 10 wt%, at which it reached the lowest value. After that, it began to increase again. On the other hand, the separation factor, and total flux of the PEBA/ZSM-5 membrane containing 10 wt% ZSM-5, PEBA/ZSM-5-10, increased with the increase of feed concentration and temperature. The best PV performance, separation factor and total flux of PEBA/ZSM-5-10 membrane were 185.5 and 199.5 gm−2h−1, respectively, with feed concentration of 5 wt% EA at 50°C.